GE_GERICHTE P/25362/2018 vom 4. Oktober 2021 - GE Cour de justice (2021)
IN DUBIO PRO REO;CONTRAINTE SEXUELLE;TENTATIVE(EN GÉNÉRAL);RESPONSABILITÉ RESTREINTE(DROIT PÉNAL);APPEL JOINT ;FIXATION DE LA PEINE | CP.189; cp.19.al2; CP.54; CP.47